Putting Pottery in Place: A Social Landscape Perspective on the Late Formative Upper Desaguadero Valley, Bolivia - Rivas-Tello, Daiana (My University, 2017)
Recent archaeological investigations demonstrate that landscapes of the past are not just passive backdrops to people's practices, but rather play a key role in social, cultural, political, and economic processes. Archaeologists have typically studied landscapes by analysing settlement patterns and architecture, yet newer approaches include the study of production practices such as pottery or stone-tool production. One such approach focuses on the ‘taskscape’, which includes skilled agents, and daily tasks occurring on the landscape. Scholars using this framework consider the rhythms and the embodied experience of people in specific places, and explore both the social relationships and ecological affordances of landscapes. Archaeologists, in particular, have considered the embedded nature of daily tasks performed on the landscape, and the material remains of these tasks. In this project I focus on the taskscapes of the Late Formative Period (200 B.C.- A.D. 500), in the Upper Desaguadero Valley, just south of Lake Titicaca in Bolivia. Little is known of Late Formative landscapes, a period prior to the rise of the Tiwanaku state. I study Upper Desaguadero landscapes to contribute to scholarship exploring the social, political and economic changes of the Late Formative Period, prior to the emergence of the Tiwanaku state. I study ceramics from two recently excavated sites, Khonkho Wankane and Iruhito. My research explores the difference between Khonkho Wankane and Iruhito taskscapes and whether this is evident through ceramics. Potters’ choices during production are based on their taskscapes, which can affect the materials selected for the paste (the mixture of clay and inclusions), to how the vessels were decorated. Pottery was not only made but also used during daily tasks and thus pottery usage can be used to examine taskscapes. I conduct attribute analysis, with particular attention to paste. For a more detailed analysis of paste I employ a Dino-Lite digital USB microscope. The digital USB microscope is portable, affordable and time efficient, allowing for analysis to be conducted in the field. This method is promising for ceramic analysis, as it encourages standardization and inter-site comparisons. Ultimately, this tool provides quick yet detailed insights into past social landscapes.
Keywords: Archaeology; Landscape Studies; Ceramics; Andean Archaeology; Bolivia; Lake Titicaca; Paste Analysis